Beating Vesicles: Encapsulated Protein Oscillations Cause Dynamic Membrane Deformations. Issue 50 (20th November 2018) - Litschel, Thomas; Ramm, Beatrice; Maas, Roel; Heymann, Michael; Schwille, Petra
Abstract: The bacterial Min protein system was encapsulated in giant unilamellar vesicles (GUVs). Using confocal fluorescence microscopy, we identified several distinct modes of spatiotemporal patterns inside spherical GUVs. For osmotically deflated GUVs, the vesicle shape actively changed in concert with the Min oscillations. The periodic relocation of Min proteins from the vesicle lumen to the membrane and back is accompanied by drastic changes in the mechanical properties of the lipid bilayer. In particular, two types of oscillating membrane‐shape changes are highlighted: 1) GUVs that repeatedly undergo fission into two connected compartments and fusion of these compartments back into a dumbbell shape and 2) GUVs that show periodic budding and subsequent merging of the buds with the mother vesicle, accompanied by an overall shape change of the vesicle reminiscent of a bouncing ball. These findings demonstrate how reaction–diffusion‐based protein self‐organization can directly yield visible mechanical effects on membrane compartments, even up to autonomous division, without the need for coupling to cytoskeletal elements. Abstract : Active vesicles : Min proteins were encapsulated in giant liposomes. This not only caused the proteins to self‐organize and form oscillatory, spatiotemporal reaction–diffusion patterns on the vesicle membranes, but also had an unexpected effect on lipid bilayer dynamics: The periodic binding and disassociation of the proteins to and from the membrane induced changes in membrane curvature, leading to oscillations in the overall shape of the vesicles.